2017
DOI: 10.14528/snr.2017.51.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Differences in alcohol consumption habits between Roma and non-Roma in Northeastern Slovenia

Abstract: Introduction: Slovenia has a high level of alcohol consumption. Comparisons of the alcohol drinking habits of the Roma and non-Roma population have yielded conflicting results. The aim of this research was to compare alcohol consumption habits between Roma and non-Roma in a sample population in Northeastern Slovenia. Methods: We conducted a cross-sectional study in which we included 100 representatives of Roma and 100 representatives of non-Roma population, aged 18 to 65 years. The questionnaire u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Comparing the alcohol behavior of the Hungarian general and Roma populations in our study suggests that although Roma people consume alcohol at lower frequencies, they experience more alcohol-related harm, even when considering past problems. This is congruent with the findings from Slovenia by Zelko et al which is the only research available on Roma using the AUDIT questionnaire ( 49 ). Furthermore, studies in Europe also indicate that alcohol-related harm affects certain groups disproportionately, with the harm increasing with lower socioeconomic status, though mostly accompanied by lower consumption levels ( 9 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Comparing the alcohol behavior of the Hungarian general and Roma populations in our study suggests that although Roma people consume alcohol at lower frequencies, they experience more alcohol-related harm, even when considering past problems. This is congruent with the findings from Slovenia by Zelko et al which is the only research available on Roma using the AUDIT questionnaire ( 49 ). Furthermore, studies in Europe also indicate that alcohol-related harm affects certain groups disproportionately, with the harm increasing with lower socioeconomic status, though mostly accompanied by lower consumption levels ( 9 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, gender-specific results were obtained from a preceding study, where young Spanish Roma men were more likely to drink alcohol compared to other young men, whereas among women, alcohol consumption was less frequent among Roma than in the general population ( 48 ). Comparing the alcohol consumption habits of the Roma and non-Roma populations in Slovenia using the Alcohol Use Disorders Identification Test (AUDIT) revealed that although the Roma scored lower overall on the AUDIT and were characterized by a higher proportion of teetotalers, they also had a lower proportion of non-hazardous drinkers ( 49 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol consumption patterns and related harm vary not only across countries but also within the same country among ethnic groups [ 9 ], including the most disadvantaged Roma population of Europe and Hungary [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. This minority population is mainly accumulated in Central and Eastern Europe [ 23 ] with a representation of over 5% of the total population [ 24 ] (8.9% of the total population, 876,000 individuals in 2013 in Hungary [ 25 ]) and faces discrimination, several barriers when seeking healthcare services, and poorer health outcomes compared to mainstream populations [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%